A comparative study of postgraduate theses in pedagogy and preschool education in Austria and Turkey - Pınar, Yunus; Gür, Dilek; Pınar, Nihal Kubilay; Demir, Kemal; Iltar, Ekin Kaynak; Songören, Sevgi Arkılıç; Özenici, Salih (Frontiers in Psychology, 2023)
In this study, postgraduate theses in the fields of pedagogy and preschool education in Austria and Turkey are compared in terms of factors such as similarity index, research designs and quality of academic writing. To achieve this goal, a commonly-used web-based plagiarism detection service was used to determine the similarity indexes of 258 theses prepared in the two countries (124 from Austria, 134 from Turkey) by checking them against existing sources such as articles, theses, and books; and a relational screening model was used to determine the degree of correlation among variables. In addition, the research topics, research designs, and data collection tools employed in each thesis were identified and content analysis was performed on selected theses with an eye to gaining a sense of the methodological approaches used in pedagogy in Austrian and Turkish universities and making comparisons between the two countries. Our results suggest that the mean similarity index between the postgraduate theses in Austria is 8.78 (Std. Dev. 4.91), while the mean similarity index between the postgraduate theses prepared in Turkey is 25.10 (Std. Dev. 9.85). Our analysis indeed indicates that 91% (n 113) of the theses prepared at Austrian universities and only 13% (n 17) of the theses prepared at Turkish universities did not exceed the acceptable similarity index of 15%. The fact that 87% of the theses written in Turkey are dramatically similar to the available resources shows that many of the studies carry potential risks in terms of originality. The findings of our content analysis revealed that 94% of the studies conducted in Austria are comprised of studies with a qualitative design and 33% of the studies conducted in Turkey are comprised of qualitative studies. Our findings also suggest that a variety of qualitative studies such as observations according to Tavistock Model, videography, video analysis, problem-centered interviews, narration interviews, content analysis, ethnography, hermeneutics, grounded theory, biographical methods, case studies were used in Austria. It should be noted that the majority of the studies conducted in Turkey employ a qualitative and quantitative method without a direct focus on children,